Cost-effectiveness of implementing 13-valent pneumococcal conjugate vaccine for U.S. adults aged 19 years and older with underlying conditions - Miwako Kobayashi; Charles Stoecker; Wei Xing; Bo-Hyun Cho; Tamara Pilishvili (Taylor & Francis Group, 2021)
In June 2019, the Advisory Committee on Immunization Practices (ACIP) changed the recommendation for routine 13-valent pneumococcal conjugate vaccine (PCV13) use in immunocompetent adults aged ≥65 years, including those with select chronic medical conditions (CMC). ACIP now recommends PCV13 for this group of adults based on shared clinical decision-making. Because adults with CMC continue to be at increased risk for pneumococcal disease, we assessed the cost-effectiveness of administering PCV13 in series with the recommended 23-valent pneumococcal polysaccharide vaccine (PPSV23) for adults aged ≥19 years with CMC. We used a probabilistic model following a cohort of 19-year-old adults. We used Monte Carlo simulation to estimate the impact on program, medical, and non-medical costs (in 2017 U.S. dollars [$], societal perspective), and pneumococcal disease burden when administering PCV13 in series with PPSV23. We used PCV13 efficacy and post-licensure vaccine effectiveness (VE) data to estimate VE against PCV13 type disease (separately for disease by serotype 3 [ST3], the most common PCV13 type, and all other PCV13 serotypes). We considered a range of estimates for sensitivity analyses. Analyses were performed in 2019. In the base case, assuming no PCV13 effectiveness against ST3 disease, adding a dose of PCV13 upon CMC diagnosis cost $689,299 per QALY gained. This declined to $79,416 per QALY if VE against ST3 was estimated to be equivalent to other PCV13-types. Administering PCV13 in series with the recommended PPSV23 for adults with CMC was not cost saving. Results were sensitive to estimated PCV13 VE against ST3 disease.